INFLUENCE OF DOSE AND POWER OF IONIZING RADIATION ON THE DYNAMICS OF THE COPPER CONTENT IN THE ANIMAL BLOOD - Петрина, Л. Г.; Мойсеєнко, М. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The content changes of copper in blood of the Wistar rats after single irradiation with γ-quant in doses of 1.0, 5.0 and 9.0 Gy from source 60Co at dose rates of 0.001; 0.01; 0.1 and 1.0 Gy/min have been investigated. The study was conducted after 0.5, 1, 2, 4, 6, 8, 10, 15, 20, 25, 30 days after radiation. The aim of the work was to study the influence for both small and high doses of ionizing radiation at different exposure modes on the dynamics of the copper content in the blood of rats during long time. It was found that the change in concentration of microelement, held under irradiation at doses of 1,5 and 9 Gy, had the character of a positive balance for 6-15-30 days. The magnitude of these changes, their direction and duration of display dependent on dose and radiation power. In all animals groups the concentration of copper in blood reached maximum values at 6-15 days and in the group of animals irradiated in a dose of 9.0 Gy, copper levels rise before 15th day. Data of our study represents theoretical interest, because contributing to the knowledge of biochemical mechanisms of radiation injury and in this regard, and the pathogenesis of radiation sickness, and practical interest for the knowledge of radiation damage mechanisms is a prerequisite for sustainable development of prevention and treatment of radiation sickness. The results of the dynamics of copper content in the development of radiation effect can be used to develop new methods of complex treatment of radiation sickness as well as in the use of X-therapy.